Interfacial Strain Gradients Control Nanoscale Domain Morphology in Epitaxial BiFeO3 Multiferroic Films. (6th April 2020) - Sando, Daniel; Han, Mengjiao; Govinden, Vivasha; Paull, Oliver; Appert, Florian; Carrétéro, Cécile; Fischer, Johanna; Barthélémy, Agnès; Bibes, Manuel; Garcia, Vincent; Fusil, Stéphane; Dkhil, Brahim; et al.
Abstract: Domain switching pathways fundamentally control performance in ferroelectric thin film devices. In epitaxial bismuth ferrite (BiFeO3 ) films, the domain morphology is known to influence the multiferroic orders. While both striped and mosaic domains have been observed, the origins of the latter have remained unclear. Here, it is shown that domain morphology is defined by the strain profile across the film–substrate interface. In samples with mosaic domains, X‐ray diffraction analysis reveals strong strain gradients, while geometric phase analysis using scanning transmission electron microscopy finds that within 5 nm of the film–substrate interface, the out‐of‐plane strain shows an anomalous dip while the in‐plane strain is constant. Conversely, if uniform strain is maintained across the interface with zero strain gradient, striped domains are formed. Critically, an ex situ thermal treatment, which eliminates the interfacial strain gradient, converts the domains from mosaic to striped. The antiferromagnetic state of the BiFeO3 is also influenced by the domain structure, whereby the mosaic domains disrupt the long‐range spin cycloid. This work demonstrates that atomic scale tuning of interfacial strain gradients is a powerful route to manipulate the global multiferroic orders in epitaxial films. Abstract : The domain morphology in multiferroic BiFeO3 films is shown to depend on the strain profile across the film–substrate interface. Strong interfacial strain gradients induce mosaic domains, while uniform strain across the interface yields stripe domains. Ex situ annealing of mosaic domain samples induces stripe domains. The magnetic order is also affected, with mosaic domains disrupting the long‐range spin cycloid.